Evaluación de susceptibilidad de Tetranychus urticae, a acaricidas en el cultivo de pimiento (Capsicum annuum) - Calderón Calixto, Edison Stalin (2022)
The misuse of acaricides has generated resistance for the control of Tetranychus urticae K. in the bell pepper crop (Capsicum annuum L.) in addition to generating economic losses and reducing yields. The objective of the study was to evaluate the susceptibility of the pest Tetranychus urticae K. to three acaricides in a bell pepper crop in the laboratory phase. Within the methodology, two different populations were evaluated: Population 1 (resistant or high pressure), collected in the community of Chalguayacu belonging to the canton of Pimampiro, province of Imbabura and Population 2 (susceptible or low pressure), collected in the community of Paragachi belonging to the same canton. The variables evaluated were: adult mite mortality, viable and non-viable eggs. A factorial design a x b x c +1 (population x acaricide x dose + absolute control) was used, with three replicates. The acaricides used for this research were: Spiromesifen, Chlorfenapyr and Etoxazol\; the concentrations used were set at +25% and - 25% of the commercial dose to measure the efficacy and resistance index of the pest. The application period for the three products was 24,48,72 and 96 hours, respectively. The best result obtained in this research for the variable mite mortality was 84% with the ingredient Chlorfenapyr at 96 hours of application, with the dose +25% of the recommended dose. For the viable eggs variable, the lowest percentage was obtained with the ingredient Etoxazole with 0.9%. Therefore, this research allowed to determine that in susceptible populations it is possible to apply lower doses than recommended and for resistant populations it can be increased up to 25% of the dose established by the manufacturer.